‘Irfâniy as Epistemology Method Sufism Based on Conscience - Yogi Prasetyo; Absori Absori (TSAQAFAH, 2018)
This article aims to explain ‘irfâniy as a method for human beings to acquire knowledge through the intuition of conscience as did the Sufis through the path of Sufism in the teachings of Islam. Man as a battle creature given the highest degree by God, in addition to the sense and sense, also given the conscience to feel things that are not real in concrete and something that is outside the logic. ‘Irfâniy as a method of knowledge epistemology can lead man to a spiritual life close to God. The inner nature of the knowledge of ‘irfâniy has led man to an immaterial life which is sublime in the true life of the world. The path of Sufism’s life which is done by the ‘irfâniy method is able to place the life of ma‘rifat for man, that is, the highest level of life associated with a very close relationship with God. There are several steps that must be taken by humans to achieve ‘irfâniy knowledge, starting from the preparation stage, acceptance, formation and disclosure. Therefore, the subjective nature of ‘irfâniy knowledge, then the quality of knowledge depends on the human ability to perform by the mind. ‘Irfâniy as a form of human inner knowledge is influenced by the empirical and logical experience and spiritual life of the deity of man, so that knowledge ‘irfâniy is direct, whole, fixed and comprehensive. Humans with ‘irfâniy method can reach God truth that is absolute and essential.